Contact line friction in liquid-liquid displacement on hydrophobic surfaces - Ramiasa, M.; Ralston, J.; Fetzer, R.; Sedev, Rossen (American Chemical Society, 2011)
The dynamics of a receding water front displaced by (a) an immiscible droplet of dodecane and (b) an air bubble on smooth thiol and silane coated substrates has been investigated. For velocities below 0.02 m/s, the three phase contact line motion is captured by the molecular kinetic theory. The corresponding wetting parameters show a dependence on surface hydrophobicity, irrespective of the substrate chemistry. The contact line frictions for both liquid-liquid and liquid-vapor systems are directly compared by using an existing approach and a new model that adds the contributions of the individual fluid viscosities. For both systems, the contact line friction increases with the affinity of the fluids for the substrate. Three phase contact line motion occurs via the concerted movement of clusters of molecules or contact line segments, rather than through individual molecular displacements.